Pedro Calderón de la Barca, Judas Macabeo. Edición crítica de las dos versiones, ed. F. Rodríguez-Gallego - Fernando Plata (Universitat Autònoma de Barcelona, 2013)
Reseña de Pedro Calderón de la Barca, Judas Macabeo. Edición crítica de las dos versiones, ed. F. Rodríguez-Gallego, Universidad de Navarra / Iberoamericana / Vervuert (Biblioteca Áurea Hispánica, 80; Comedias Completas de Calderón, 8), Madrid / Frankfurt, 2012, 501 pp. ISBN: 978-84-8489-692-0.